Carbon2Chem®-CCU as a Step Toward a Circular Economy - Wich, Teresa; Lueke, Wiebke; Deerberg, Goerge; Oles, Markus (Frontiers in Energy Research, 2020)
With respect to the climate goals of the Paris agreement, different carbon dioxide (CO2) reduction strategies are discussed for industrial processes. For a comparison of these strategies – carbon direct avoidance (CDA), carbon capture and storage (CCS) and carbon, capture and utilization (CCU) – a holistic view is mandatory. In this article recent literature is at first analyzed for stringent methodology, transparency and applied assessment criteria. Secondly, a new set of assessment criteria is presented: Beside the carbon reduction potential, the energy demand and costs, additional criteria for the mid-term impact of a CO2 reduction strategy like the reuse potential or social acceptance are analyzed. In a third step, publicized data is converted into consistent system boundaries. Deriving from the life cycle assessment (LCA) the method “system expansion” is selected. The impact of the system expansion approach is demonstrated by calculation of the CO2 and the energy balances of the CCU approach within different system boundaries. The system expansion is visualized systematically under the consideration of the different processes. The Carbon2Chem® project is described as one example for the CCU approach of the steel and chemical production, which offers a CO2 reduction of about 50 %. Additionally the CO2 reduction potential is expandable proportional with increasing utilization of top gases. A consistent level of the energy demand for the CCU approach is shown compared to the conventional production processes of steel and chemicals.